Architectural heritage as filming location: impact on identity and significance - Tejashree Lakras (Built Heritage)
Abstract Using architectural heritage sites as filming locations has unintended and diverse effects on the sites and their relationships with stakeholders. While this phenomenon has attracted scholars largely from the heritage domain and film-induced tourism (hereafter FIT) discourse, the research has been minimal, is still evolving, and is located primarily in the global west; thus, more research in this area is needed. This paper responds to such gaps in the literature by studying a case from India, where scholarly knowledge on this phenomenon is scarce, available only in the FIT literature, and lacks a heritage conservation viewpoint. The selected case, the College of Agriculture in Pune, which has a colonial period structure and is one of the oldest educational institutes in India, has been officially branded as a filming location by the Film Facilitation Cell and Maharashtra Tourism Development Corporation. It has experienced a sudden rise in affection from its stakeholders and an upsurge in filming productions after its appearance in Bollywood’s blockbuster film Munna Bhai M.B.B.S. (Hirani, 2003). Such activities have tended to impact the perceptions of stakeholders about the historical identity and architectural significance of the site and, ultimately, its conservation. The study presents this impact using qualitative methods, including focus group discussions and personal interviews of stakeholders: management staff, teachers, students, heritage walk leaders, and tourists. The responses were simultaneously juxtaposed with the film analysis method, giving rise to the interpretive themes of pride, narratives, celebrity associations, and architecture and planning. The research findings reveal that the stakeholder’s overall approach prioritises the site as an ideal filming location over its historical identity, compromising the ethics of heritage conservation and, thus, overshadowing the site’s architectural significance. Studying other effects of this phenomenon, such as heritage conservation challenges and FIT management, is beyond the scope of this paper. This study, therefore, is a preliminary step in this understudied area and establishes the pressing need for more rigorous and holistic knowledge production in heritage discourse, particularly in India.